(untitled) (International Journal of Engineering and Computer Science, 2017)
Mobile Ad Network is a self-configuring infrastructure less network of wireless communication. Opportunistic routing is a recent technique that achieves high throughput in the face of lossy wireless links. The current opportunistic routing protocol, ExOR, ties the MAC with routing, imposing a strict schedule on routers’ access to the medium. The main concept of cooperative communications is to make use of the broadcast nature of the wireless medium. In this paper, we are improving the performance of cooperative opportunistic routing in MANET using spatial reuse. Here MORE is used instead of ExOR, since ExOR ties the MAC with routing, adding a strict schedule on routers’ access to the medium. It randomly mixes the packets before forwarding them. This randomness ensures routers that hear the same transmission do no forward the same packets. Thus, MORE has no needs special scheduler to coordinate routers and can run directly on top of 802.11.